Stakeholder Perception of Health Resources and Village-Funds Optimizing for Maternal and Child Health Program - Sriatmi, Ayun; Jati, Sutopo Patria; Martini, Martini; Mustofa, Syamsulhuda Budi; Budiyono, Budiyono (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
The low support on cross-sectoral commitment of village stakeholders to health programs was one of factors contributed maternal and infant mortality in Tegal Regency. Although village funds have been rolled out since 2015, its implementation hadn’t been optimal due to orientation focus on infrastructure development. The study aims to analyze perceptions and attitudes of village stakeholders towards village level resources and optimizing village funds for MCH programs based on 3 groups stakeholder (Decision Maker, Provider and Clients-Representatives). It’s quantitative research, population of all village level stakeholders with 300 people as samples from 30 selected villages. Data collected with interview using questionnaire and being analyzed with frequency distribution and statistically using Kruskal-Wallis test. Most of three group stakeholders had good perception of their health resources and positive attitude towards MCH programs, but different results were seen for attitudes towards optimizing village funds. Decision Maker group and Clients-Representatives group showed tendency refusing, while Provider group tend to agree on village funds optimizing for MCH programs. Statistically, there were differences in attitudes towards optimizing village funds for MCH program between three groups. Attitude differences was mainly due to lack of understanding from external health stakeholders about health programs, especially village’s MCH program.